2017
DOI: 10.1108/jstpm-05-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing sustainable urban development through smart city applications

Abstract: Purpose This paper investigates the potential contribution of smart city approaches and tools to sustainable urban development in the environment domain. Recent research has highlighted the need to explore the relation of smart and sustainable cities more systematically, focusing on practical applications that could enable a deeper understanding of the included domains, typologies and design concepts, and this paper aims to address this research gap. At the same time, it tries to identify whether these applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
161
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(185 citation statements)
references
References 48 publications
2
161
0
1
Order By: Relevance
“…Sustainable development goals and smart targets should be well understood with respect to their synergy and integration (see, e.g., [1,5,9,12,13,16,19,43]) in the context of city planning, a valuable force for attaining a sort of integrated objectives in the realm of smart sustainable cities. As a management and government function, city planning involves formulating a detailed plan to achieve optimum balance of demands for growth with the available resources and the need to protect the environment, or to provide and maintain a livable and healthy human environment in conjunction with minimal demand on resources and minimal impacts on the environment-by integrating urban strategies with technological innovations as well as formulating and implementing policy regulations and institutional frameworks.…”
Section: Strategic Smart Sustainable Urban Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustainable development goals and smart targets should be well understood with respect to their synergy and integration (see, e.g., [1,5,9,12,13,16,19,43]) in the context of city planning, a valuable force for attaining a sort of integrated objectives in the realm of smart sustainable cities. As a management and government function, city planning involves formulating a detailed plan to achieve optimum balance of demands for growth with the available resources and the need to protect the environment, or to provide and maintain a livable and healthy human environment in conjunction with minimal demand on resources and minimal impacts on the environment-by integrating urban strategies with technological innovations as well as formulating and implementing policy regulations and institutional frameworks.…”
Section: Strategic Smart Sustainable Urban Planningmentioning
confidence: 99%
“…Regardless, this endeavor should consist in adopting a holistic approach to decision-making, a pathway that can best be pursued by employing advanced technological systems and analytical methods, thereby the need for big data technologies and related data-driven decision-making with respect to urban policy design and analysis. As noted by Angelidou et al [5], the incorporation of the systematic use of big data in the policy development and monitoring process is a key success factor towards better policy design and implementation, with significant positive impacts on contemporary cities on multiple levels. To put it differently, new sources of urban data coordinated with urban practice and policy can be applied on the basis of the fundamental principles of data science and analytical engineering to devise powerful solutions to urban sustainability problems.…”
Section: Strategic Smart Sustainable Urban Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…2 by referring to the study of U.S. Department of Homeland Security [4], Lacinak & Ristvej [7], McClellan et al, [8], and Angelidou et al, [9]. …”
Section: Risk Factors Of Smart Citymentioning
confidence: 99%
“…Angelidou et al, [9] defined risk factors and suggested mitigation strategies considering the environmental aspects of possible risks in smart cities.…”
Section: Risk Factors Of Smart Citymentioning
confidence: 99%